Feeding Behavior and Preferences of Hemiplecta humphreysiana and Lissachatina fulica (Gastropoda) to Support Heliciculture in Indonesia - Jessima Pratiwi; Fuji Anandi; Pamungkas Rizki Ferdian; Tri Hadi Handayani; Raden Lia Rahadian Amalia; Narti Fitriana; Ayu Savitri Nurinsiyah (Jurnal Biodjati, 2022)
The trend of Heliciculture for human consumption, animal feed, medicine, and neutricosmeceutical is rising globally. To gain a better knowledge on the Heliciculture of Indonesian land snails, we studied the daily activity with a focus on feeding behavior and the feed preference of two land snail species Hemiplecta humphreysiana (HH) and Lissachatina fulica (LF). The two species were selected because of their abundancein nature, as well as to compare behavior and preference between native (HH) and invasive (LF) species. Three days of daily activity observation was conducted by using a scan animal sampling method with 5 minutes intervals towards three individuals of HH and LF. The experiment on feeding preference was conducted towards ten individuals per species in 28 days of observation (14 days each for vegetables and fruits). Each individual was placed in different rearing boxes. A multiple-choice test method was applied and consisted of two treatments i.e. vegetable treatment (pakcoy, chicory, lettuce, cabbage) and fruit treatments (mango, cucumber, melon, papaya). The nutritional value from the observed feed was also analyzed. Based on the total of 51,840 minutes of observation records, both species were generally active from 21.00-03.00. HH was more active in moving when given vegetable treatment. The species preferred to feed on cucumber, melon, lettuce, and pakcoy. LF was more active in moving and feeding when treated with fruits. The species is more adaptive when given new feed and likes all four fruits, but preferred lettuce in the vegetable treatment. Both species prefer to feed with relatively high protein, high fiber, and moderate total carbohydrate content. Providing the right feed and at the right time can support the effectiveness of Heliciculture.